Instagram and Twitter new era information propagator: A study - Shopita Khurana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The new age digital era where the propagation of information through social media platform is so strong as now people to get updates or no more only dependent upon the newspaper and news channels as the magic of information dissemination through social networking sites like twitter and Instagram disseminate the information in a lightning speed. In previous days the major platform to get the information were newspapers, magazine, news channel and radio. With the advent of new media, the universe to disseminate the information has widen its horizon, now the audience can get both information with entertainment also. In the earlier age of new media, specially the social media platform, the platform was only considered to be used as the source of entertainment and connecting to friends and family, but now a days these social media sites are not only limited to entertainment but also work as a source of information. Out of so many social sites performing these functions, twitter can be said as the most powerful tool. The advent of these social media platform has given birth to the concept of infotainment where the information is transmitted by these platforms in the entertaining way. The following study talks about the popularity gained by the social media platform as an agent to propagate information over the traditional media. the qualitative method of research has been implemented to study the same.